2016
DOI: 10.3389/fimmu.2016.00475
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Toxicants-Induced Immune Responses in the Olfactory Mucosa

Abstract: Olfactory sensory neurons (OSNs) are the receptor cells for the sense of smell. Although cell bodies are located in the olfactory mucosa (OM) of the nasal cavity, OSN axons directly project to the olfactory bulb (OB) that is a component of the central nervous system (CNS). Because of this direct and short connection from this peripheral tissue to the CNS, the olfactory system has attracted attention as a port-of-entry for environmental toxicants that may cause neurological dysfunction. Selected viruses can ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 81 publications
1
53
0
2
Order By: Relevance
“…Nasal airflow reduction, edema‐induced compression of olfactory nerves, or hypersecretion of Bowman's glands with altered ion concentrations in the olfactory mucus likely contribute to reducing the sense of smell . It has also been suggested that inflammatory mediators could have direct neurotoxic actions on olfactory sensory neurons (OSNs) . OSNs with abnormal morphologies and potential functional defects, as well as higher numbers of immature neurons, suggesting an attempt at regeneration, have also been reported in CRS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Nasal airflow reduction, edema‐induced compression of olfactory nerves, or hypersecretion of Bowman's glands with altered ion concentrations in the olfactory mucus likely contribute to reducing the sense of smell . It has also been suggested that inflammatory mediators could have direct neurotoxic actions on olfactory sensory neurons (OSNs) . OSNs with abnormal morphologies and potential functional defects, as well as higher numbers of immature neurons, suggesting an attempt at regeneration, have also been reported in CRS patients.…”
Section: Introductionmentioning
confidence: 99%
“…The IL-1 receptor IL-1R is ubiquitously expressed in virtually all cell types and is a key signaling receptor for the IL-1 family of inflammatory cytokines (35). As an endogenous IL-1 receptor antagonist, IL-1RA may play critical roles in shutting down IL-1R signaling in the nasal respiratory tissues and the olfactory mucosa to inhibit allergen-and/or infection-induced inflammatory responses (7). The high levels of IL-1RA are likely needed to protect the tissues from inflammation-related injury.…”
Section: Resultsmentioning
confidence: 99%
“…Decades of exposure to air-borne environmental agents may also contribute to age-related olfactory loss (7). However, the molecular aspects of aging-associated olfactory loss in humans are not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations